Cases on healthcare information technology for patient care management - Sarnikar, Surendra, 1977-; Bennett, Dorine, 1957-; Gaynor, Mark, 1956-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book highlights the importance of understanding the potential challenges and lessons learned from past technology implementations of health information technologies"--Provided by publisher.
Doing and understanding: use of case studies for health informatics education and training / Cynthia LeRouge ... [et al.] -- Individual, organizational, and technological barriers to EHR implementation / Matthew J. Wills -- One system of care, one electronic chart / Jennifer Gholson, Heidi Tennyson -- Big information technology bet of a small community hospital / Sergey P. Motorny -- Physician interaction with EHR: the importance of stakeholder identification and change management / Cherie Noteboom -- Primary care patient management and health information technology / Nina Multak -- Good IT requires good communication / Charles H Andrus, Mark Gaynor -- Telehealth implementation: the voice of experience / Mary DeVany ... [et al.] -- Avera medical group pierre's implementation of an econsult program: bringing specialty practices to patients in rural South Dakota / Ann Pommer -- Florida health information exchange: a journey to improving care through the exchange of patient health information / Alice Noblin, Kelly McLendon, Steven Shim -- Health information technology collaboration in community health centers: the Community Partners HealthNet, Inc. / Elizabeth J. Forrestal ... [et al.] -- CoRDS registry: an HIT case study concerning setup and maintenance of a disease registry / Seth Trudeau -- Healthcare systems using clinical data: addressing data interoperability challenges / Biswadip Ghosh -- User and data classification for a secure and practical approach for patient-doctor profiling using an RFID framework in hospital / Masoud Mohammadian, Ric Jentzsch -- Application of handheld computing and mobile phones in diabetes self-care / Abdullah Wahbeh -- Mobile device application in healthcare / Sandeep Lakkaraju, Santhosh Lakkaraju -- Clinical decision support system for diabetes prevention: an illustrative case / Sarin Shrestha.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed January 17, 2013).
Keywords: Medical informatics -- Case studies; Nursing services -- Administration -- Case studies; Medical Informatics; Patient Care Management -- methods; Clinical decision support systems; Clinical intelligence and analytics; Computerized provider order entry; Electronic medical records; Health information exchange; Security and privacy issues in HIT implementations; Social media in healthcare; Telemedicine; Electronic books